A 343 Italian cohort of patients analysed with array‐comparative genomic hybridization: unsolved problems and genetic counselling difficulties. Issue 9 (2nd August 2021) - Palka Bayard de Volo, C.; Alfonsi, M.; Morizio, E.; Guaciali‐Franchi, P.; Mohn, A.; Chiarelli, F.
Abstract: Background: The recent introduction of microarrays for genetic analyses has allowed higher etiological diagnostic rates in patient with intellectual disability (ID), autism spectrum disorders (ASD), epilepsy and multiple congenital anomalies (MCA), because of its resolution. This approach still results of high complexity and some limitations have been reported. In fact, it discloses several variants of unknown significance (VOUS) or incidental findings. In all cases, a massive amount of data is generated, because of this, the analysis and the interpretation is very difficult and often without a definitive conclusion. Method: We analysed an Italian cohort of 343 patients with ID, MCA and ASD by array‐comparative genomic hybridization. The purpose of this work was to consider the proportion of the chromosomal abnormalities in such cohort and to assess the distribution of the different type of the chromosomal abnormalities concerning their pathogenic significance, their origin and their correlation to these clinical phenotypes. Results: Array‐comparative genomic hybridization analysis revealed 76 positive results. Abnormalities were detected in 27.8% of patients with ID, 11.1% with ASD, 10.7% with epilepsy and 19.4% with multiple congenital anomalies. The anomalies were classified in three major groups: group 1 (27 patients) with pathogenic alterations (P group); group 2 (34 patients) with VOUS potentially pathogenic (PP group); and group 3 (13 patients) with VOUS potentially benign (PB group). As expected, comparing the diagnostic groups, we observed a greater number of deletions in the P group and that all the abnormalities of the PB group were inherited. Conclusions: Our retrospective study resulted in confirming the high detection rate of microarrays. CNV classification remains a complex procedure. The difficulty in CNV classification points out the importance of the patient selection, helping the interpretation of the molecular cytogenetic results.